A Note on the Growth of Meromorphic Functions with a Radially Distributed Value - Jun-Fan Chen (Abstract and Applied Analysis)
This note is to investigate the growth of transcendental meromorphic functions with radially distributed values. We generalize a more recent result of Chen et al. (2011). The paper is closely related to some previous results due to Fang and Zalcman (2008), and Xu et al. (2009).